Analysis of Factors That Motivate Entrepreneurial Women Through Online Business (Study on Residents of Lamongan District) - Noer Rafikah Zulyanti (Enrichment : Journal of Management, 2020)
The economic well-being of the community is measured from the level of entrepreneurship. This will happen if all family members have their own income to fulfill their needs. The purpose of this study is to determine the partial and simultaneous influence of factors that affect the interest in entrepreneurship online in women. This type of research is quantitative. with a total population of 276 and a sample of 86 respondents. The analytical test tools used include validity, reliability, multiple regression t test and F test. The results obtained are freedom in work (X1), business opportunities (X2), personal pleasure (X3 ), financial security (X4) and social status (X5) that encourage interest in entrepreneurship online have partial and simultaneous effect. This is evidenced by the t test value is greater than the t table value and the calculated F value is greater than the F table. and the most dominant variable is the opportunity factor variable as evidenced by the highest regression coefficient value compared to other variables.